Probiotics in inflammatory bowel diseases: emphasis on mechanisms and clinical application - Junxiang Zhang; Junxiang Zhang; Xiaoman Zhang; Xiaoxin Cheng; Shijin Wang; Yangxuan Lv; Xu Zheng; Guangzhen Wu (Frontiers in Medicine)
Inflammatory bowel disease (IBD) is a group of diseases characterized by chronic intestinal inflammation including Crohn’s disease (CD) and ulcerative colitis (UC). In recent years, probiotics have attracted more and more attention as a potential adjuvant therapy. Probiotics can improve the symptoms and quality of life of IBD patients mainly by regulating intestinal microflora, regulating immune response, enhancing intestinal barrier function and exerting anti-inflammatory effect. However, although a large number of studies have explored the role of probiotics, there are still individual differences and uncertainties in clinical application. This paper reviews the mechanism, clinical effect and future prospect of probiotics in the treatment of IBD, and analyzes the existing clinical research and experimental data to provide reference for further research. Finally, this paper looks forward to the research direction of probiotics in the treatment of IBD, aiming at providing evidence for clinical practice.